Optimizing Mathematics Teacher Candidates' Complex Problem-Solving Skills: A Comprehensive Analysis of The Effectiveness of The Problem-Based Learning Model - Pamungkas, Megita Dwi; Rahmawati, Fadhilah; Kusuma, Jaka Wijaya; Kontoko, Kintoko; Purnomo, Eko Andy (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2024)
Complex problem solving